EU Cybersecurity Policies in Cyber-Physical Ecosystems: Challenges and Perspectives - Raffaella Brighi; Giovanna Adinolfi (European Journal of Risk Regulation)
After an introduction to the notions of cybersecurity and cybersecurity-related risks, this preface introduces four collected contributions on challenges and perspectives of EU cybersecurity policies in cyber-physical ecosystem.